Pseudodynamic tests on rubber base isolators with numerical substructuring of the superstructure and strain rate effect compensation. - Molina, F.J (Earthquake engineering & structural dynamics.)
A pseudodynamic testing procedure has been applied by which the seismic response of a base isolated building is obtained by using as specimen the isolators, while the superstructure is numerically simulated. The procedure also takes advantage of the continuous pseudodynamic testing capabilities of the ELSA laboratory, which increase the accuracy of the results and reduce the strain rate effect of the rubber bearings. A simple proportional correction of the measured forces compensates the remaining strain rate effect due to the unrealistic speed of the test. The correction factor is obtained by means of a characterizing test on the specific rubber isolators. The developed method has been successfully applied to the prediction of the seismic response of a base isolated four storey building submitted to several specified accelerograms. The results for those earthquakes as well as the effects of some changes of the parameters of the system are discussed.